"Tchaikovsky and Petipa should have seen this" Oliver Messel's desings for The Sleeping Beauty - Pritchard, Jane (Dance Books Ltd., Alton,Hampshire (UK), 2006)
Oliver Messel's desings for The Sleeping Beauty. PALABRAS CLAVE: Sleeping Beauty, Oliver Messel, stage designer.